The Role of Target’s Financial Statement Comparability in the Efficiency of Takeover Decisions - Duong, Lien; Truong, Thu Phuong (Wiley-Blackwell, 2021)
We investigate whether acquiring firms make more profitable acquisitions when target firms’ financial statements are more comparable with their industry peers. We replicate the original sample of Chen et al. (2018) and extend their sample to the most recent year. We find that acquiring firms experience higher announcement returns, higher acquisition synergies and better post-acquisition operating performance when acquiring targets with higher financial statement comparability. Our results are robust to the newly constructed measure of financial statement comparability, suggesting that comparable accounting information indeed facilitates the efficiency of capital allocation.